Kuy-e Narmak: A Resilient Heritage of Modern Housing in Tehran, Iran - Sedighi, Seyed (International Planning History Society Proceedings, 2016)
Similar to many Middle-Eastern countries during the 20th century, Iran underwent a unique process of modernisation. This process was accelerated in Tehran after the second World War, when the urban population density dramatically grew, due to rural-urban migration, and the construction of mass housing got a prominent place in the development agenda of the Iranian government. Furthermore, for creating a modern nation that made Iran part of the civilized world, the government diffused the notion of modern living through mass housing largely carried out by a group of Western-trained Iranian architects. Creating cross-cultural exchanges, they played the mediator role between the International Style and the Iranian culture, and they helped the Iranian government to purse the objectives of the development plans. Accordingly, the government established a new financial organisation named Bank-e Sakhtemani (Construction Bank) to fund new urban projects, and the parliament adopted a new law by which the arid lands beyond the border of cities were declared as state properties. Doing so braced the role of Bank-e Sakhtemani in land-use strategies, and as a result, a series of new neighbourhoods was constructed in Tehran, such as Kuy-e Narmak (1951-58), Kuy-e Nazi-Abad (1952-54), and Tehran-Pars (1958-72). Among these neighbourhoods, Narmak played a crucial role in forming modern Tehran’s Identity, and the project created a strong collective identity among its residents. Situated in the North-Eastern part of Tehran, Narmak was constructed on an area of 507 hectares, from which around 200 hectares was allocated to the public and collective amenities. This project aimed at accommodating 25,000 residents; however, it houses approximately 340,000 inhabitants, at present. To understand this adaptability, the spatial organisation of Narmak and its development should be studied. The urban layout of Narmak proposed a series of public outdoor spaces including a grid of linear gardens (Chaharbagh), and 110 enclosed gardens (Meydan) allocated to each respective block. In the block layout, houses were located around the edges of Meydans, and the repetition of this pattern provided the urban structure of Narmak. In this structure, Chaharbaghs and Meydans have become the permanent constituting a frame around which change could take place. Although these public spaces have remained unchanged, based on new needs, the inhabitants have had the possibilities to transfer their low-rise houses to mid-rise apartments, and adapt their private spaces. Therefore, by analysing Narmak’s urban form and development, this paper reveals typological elements, socio-cultural characteristics, and economic features that led to the survival and resilience of this modern urban form over times. Understanding the development of this model demonstrates whether the process of modernisation through affordable housing practices in a non-western country such as Iran presents a sense of continuity in the structure, meaning, character and identity of place, or generates a sense of disjuncture.